2007
DOI: 10.1158/1535-7163.mct-06-0399
|View full text |Cite
|
Sign up to set email alerts
|

The human IgM antibody SAM-6 induces tumor-specific apoptosis with oxidized low-density lipoprotein

Abstract: Lipids are essential for normal and malignant cells during growth and differentiation. The turnover is strictly regulated because an uncontrolled uptake and accumulation is cytotoxic and can lead to lipoapoptosis: lipoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…56 In previous studies, we demonstrated that malignant cells treated with SAM-6 antibody over-accumulate lethal depots of cholesterol and triglyceride esters. 24,25 The deadly effect of SAM-6 can be increased after addition of oxidized LDL (oxLDL). 25 This non-physiological lipid accumulation was shown to be tumor specific and always resulted in tumorspecific apoptosis or lipoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…56 In previous studies, we demonstrated that malignant cells treated with SAM-6 antibody over-accumulate lethal depots of cholesterol and triglyceride esters. 24,25 The deadly effect of SAM-6 can be increased after addition of oxidized LDL (oxLDL). 25 This non-physiological lipid accumulation was shown to be tumor specific and always resulted in tumorspecific apoptosis or lipoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The deadly effect of SAM-6 can be increased after addition of oxidized LDL (oxLDL). 25 This non-physiological lipid accumulation was shown to be tumor specific and always resulted in tumorspecific apoptosis or lipoptosis. 24,25 The exact mechanism of SAM-6 activity is not known, but is under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations